A Hierarchical Nanoparticle‐in‐Micropore Architecture for Enhanced Mechanosensitivity and Stretchability in Mechanochromic Electronic Skins. Issue 25 (9th May 2019) - Park, Jonghwa; Lee, Youngoh; Barbee, Meredith H.; Cho, Soowon; Cho, Seungse; Shanker, Ravi; Kim, Jinyoung; Myoung, Jinyoung; Kim, Minsoo P.; Baig, Chunggi; Craig, Stephen L.; Ko, Hyunhyub
Abstract: Biological tissues are multiresponsive and functional, and similar properties might be possible in synthetic systems by merging responsive polymers with hierarchical soft architectures. For example, mechanochromic polymers have applications in force‐responsive colorimetric sensors and soft robotics, but their integration into sensitive, multifunctional devices remains challenging. Herein, a hierarchical nanoparticle‐in‐micropore (NP‐MP) architecture in porous mechanochromic polymers, which enhances the mechanosensitivity and stretchability of mechanochromic electronic skins (e‐skins), is reported. The hierarchical NP‐MP structure results in stress‐concentration‐induced mechanochemical activation of mechanophores, significantly improving the mechanochromic sensitivity to both tensile strain and normal force (critical tensile strain: 50% and normal force: 1 N). Furthermore, the porous mechanochromic composites exhibit a reversible mechanochromism under a strain of 250%. This architecture enables a dual‐mode mechanochromic e‐skin for detecting static/dynamic forces via mechanochromism and triboelectricity. The hierarchical NP‐MP architecture provides a general platform to develop mechanochromic composites with high sensitivity and stretchability. Abstract : A hierarchical nanoparticle‐in‐micropore architecture in porous mechanochromic polymers enhances the mechanosensitivity and stretchability of mechanochromic electronic skins. In this device structure, stress‐concentration‐induced mechanochemical activation of mechanophores significantly improves the mechanochromic sensitivity for both tensile strain and normal force stimuli. This architecture also enables a dual‐mode mechanochromic electronic skin for detecting static/dynamic forces via mechanochromism and triboelectricity.